People Analytics - Blum, Benjamin (2021)
Modern human resources management ("people analytics") requires the use of complex algorithms and the evaluation of a vast amount of data. In this context, companies easily get into conflict with the applicable data protection regulations. The author presents the relevant provisions on data, industrial constitution and telecommunications law and uses practical case studies to show which pitfalls must be considered. In this context, he designs legally compliant solutions for the use of automated decisions, Big Data and IoT in companies. A sample works agreement on possible use scenarios is also drafted for the target group of lawyers, works councils and companies.